Seroprevalence of dengue fever among patients attending the health facilities in Kara region in Togo, 2022 - Wendpouiré I. C. Zida-Compaore; Gatibe Y.-S. Gnatou; Sibabé Agoro; Roméo Togan; Martin K. Tchankoni; Fifonsi A. Gbeasor-Komlanvi; Didier K. Ekouevi (Discover Public Health)
Abstract Background The prevalence of dengue fever is variable and is determined by geographical location and individual health status. Anti-dengue antibody seroprevalence also varied according to individual health status. In Togo, data on dengue fever is limited. In this study, we estimated the seroprevalence of dengue infections in Kara region in 2022. Methods A cross-sectional study of febrile patients who were visiting the laboratories of health facilities in Kara from March 11 to 30, 2022 was conducted. We collected blood samples from consenting patients. All sera were tested for the presence of dengue AgNS1 and anti-dengue IgM and IgG antibodies. Results Blood samples were collected from 659 patients during the survey. Median age was 26 years (Interquartile range: 18–40 years). The main symptoms that led to consultation were headache, fever, muscle aches and abdominal pain. The overall seroprevalence of dengue virus infection was 17.4% (95% CI [14.7–20.6]). Conclusion This survey strongly suggests that the dengue virus is circulating in the Kara region of northern Togo. Regular surveillance is therefore necessary to inform policy on dengue control and prevention strategies, and consequently to enhance preparedness and response to potential epidemics.